A Rare Primary Pituitary Abscess Caused by Cutibacterium Acnes - Yip, Chi-Man (Journal of Neurological Surgery Reports, 2025)
Pituitary abscess is a rare but potentially life-threatening condition with an incidence of 0.2 to 1.1% of operative pituitary lesions. Preoperative diagnosis is difficult because it shares many similarities with other pituitary lesions in terms of signs and symptoms and radiographic findings. The author would like to share a case of primary pituitary abscess due to Cutibacterium acnes infection, which is probably the first case reported in an adult patient.A 60-year-old woman with having medical history of diabetes mellitus who suffered from severe headache, fever, chillness, and vomiting in January 2024. She had been admitted to the Infectious Diseases Department; however, no definite infection source was found, but hypopituitarism was detected. Her brain magnetic resonance imaging (MRI) showed a rim-like enhanced sellar lesion with suprasellar extension. She underwent an endoscopic endonasal transsphenoidal approach with the removal of the lesion and skull base reconstruction. During the surgery, pus-like material and some solid tissue, which was yellowish white in color, were found. The culture of the pus revealed the growth of Cutibacterium acnes, and the histological report of the solid tissue proved nonneoplastic pituitary gland tissue, admixed with fibrous tissue and marked chronic inflammation. She recovered well after surgery and completed antibiotic treatment.Preoperative diagnosis of pituitary abscess is difficult. The majority of pituitary abscesses are diagnosed during the operation or postoperatively. Prompt diagnosis and treatment of pituitary abscess yield a favorable prognosis. The mainstay of treatment is transsphenoidal surgical resection in combination with antibiotic therapy.
Keywords: cutibacterium acnes; hypopituitarism; primary pituitary abscess; rim-like enhanced sellar lesion